HUBUNGAN POLA ASUH ORANGTUA DENGAN PERILAKU BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPS DI SMP NEGERI 2 PONTIANAK - Imelda Imelda; Agus Sastrawan Noor; Sri Buwono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This research aims to identify the correlation between parenting styles and the learners' learning behaviors on Social Science lessons at SMPN 2 Pontianak. This study is ex post facto research with a descriptive quantitative approach. The sample was collected using the simple random sampling technique with the Slovin formula with an error rate of 10%, involving 100 of 801 students in the population. During the research, some students whose names registered on the list were absent, and thus the substitutes were taken incidentally. The variables observed were parenting style (x) and the learners' learning behavior (y). The data were collected using questionnaires and documentation. The instrument validity was assessed by the expert, while the reliability with internal consistency was tested using the Alpha Cronbach. The Technique of data analysis used was a product-moment correlation. The findings showed that the two variables were in the medium category with the obtained data by 60% and 84%, respectively. The parenting style includes three aspects: democratic, authoritarian, and permissive. The learning behaviors include cognition, affection, and conation aspects. The correlation between the two variables was low, with the level of significance of 5% with r count value larger than r table (0.313 > 0.195). Keywords: Parenting Styles, Learning Behavior.